Product Refrigeration Load Analysis On Contact Plate Freezer On Compressor Performance At PT. Trimitra Makmur, Tarakan, North Kalimantan - Samsi, Samsi; Hermawan, Ade; Ilham, Muhammad (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
Contact plate freezer (CPF) is a cooling machine unit for freezing products which of course will maintain product freshness. In Order to runs smoothly, one thing that must be considered of the cooling system is the cooling load on the freezer contact plate. The cooling load is the amount of heat absorbed per unit time. The refrigeration cycle at PT. Trimitra Makmur uses a combined refrigeration cycle (multi-stage cycle), uses two cycles of vapor compression using two single-stage compressors. The two compressors used have the same power of 55.92 kW. The cooling load on the contact plate freezer consists of product heat load, water heat load, internal heat load, and transmission heat load. In The contact plate freezer, infiltration or heat load from the outside air are not counted because during production the contact plate freezer door is closed tightly so that the air exchange value is very small and can be neglected. In this study, the average total load on contact plate freezer 1 was 23.07079 kW, so that the average total load on the three contact plate freezers at PT. Trimitra Makmur is 69.21237 kW. The results of data collection and calculations show that the COP (Coefficient of Performance) value for the high-stage cycle is 4.33, so that the high-stage compressor power used is 1/4.33 of the cooling capacity of the contact plate freezer. Whereas in the booster cycle, a COP of 6.49 was obtained, so that the booster compressor power used was 1/6.49 of the cooling capacity of the contact plate freezer.